2017
DOI: 10.2967/jnumed.117.200006
|View full text |Cite
|
Sign up to set email alerts
|

Flortaucipir F 18 Quantitation Using Parametric Estimation of Reference Signal Intensity

Abstract: PET imaging of tau pathology in Alzheimer disease may benefit from the use of white matter reference regions. These regions have shown reduced variability compared with conventional cerebellar regions in amyloid imaging. However, they are susceptible to contamination from partial-volume blurring of tracer uptake in the cortex. We present a new technique, PERSI (Parametric Estimation of Reference Signal Intensity), for flortaucipir F 18 count normalization that leverages the advantages of white matter reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
103
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 77 publications
(111 citation statements)
references
References 29 publications
3
103
5
Order By: Relevance
“…The distinction between AD and OA may reflect acceleration of tau deposition in AD, or greater vulnerability to tau in temporoparietal cortex than prefrontal regions. 11,12 We did not observe a difference in FTP change between PiB + and PiB − groups. It is also possible that the rate of tau accumulation slows over time, similar to amyloid accumulation.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…The distinction between AD and OA may reflect acceleration of tau deposition in AD, or greater vulnerability to tau in temporoparietal cortex than prefrontal regions. 11,12 We did not observe a difference in FTP change between PiB + and PiB − groups. It is also possible that the rate of tau accumulation slows over time, similar to amyloid accumulation.…”
Section: Discussioncontrasting
confidence: 52%
“…In contrast to previous data showing a lack of FTP increase in Aβ-negative normal adults, we found that FTP increased across ROIs in our OA cohort. 12 Our results, however, indicate our approach is a robust way to measure the spatial topography of FTP change. Across the OA group, our estimates of APC were higher than previous work, which measured 0.5% APC in PiB + normal controls.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations